2020
DOI: 10.1093/nsr/nwz226
|View full text |Cite
|
Sign up to set email alerts
|

Land-surface processes and summer-cloud-precipitation characteristics in the Tibetan Plateau and their effects on downstream weather: a review and perspective

Abstract: Correct understanding of the land-surface processes and cloud-precipitation processes in the Tibetan Plateau (TP) is an important prerequisite for the study and forecast of the downstream activities of weather systems and one of the key points for understanding the global atmospheric movement. In order to show the achievements that have been made, this paper reviews the progress on the observations for the atmospheric boundary layer, land-surface heat fluxes, cloud-precipitation distributions and vertical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 73 publications
(90 reference statements)
3
62
0
Order By: Relevance
“…As "the world water tower," the Tibetan Plateau (TP) tremendously affects water budget in this region, as well as the radiation balance, weather and climate of East Asia (Chen et al, 2020;Fu et al, 2020;Wu et al, 2015;Xu et al, 2008Xu et al, , 2014, and global stratosphere (Bian et al, 2020). In the boreal summer, convection is easy to be triggered, and clouds prevail over TP (Chen et al, 2019;Li et al, 2020;Li & Zhang, 2016;Liu et al, 2015;Wang et al, 2014;Yu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As "the world water tower," the Tibetan Plateau (TP) tremendously affects water budget in this region, as well as the radiation balance, weather and climate of East Asia (Chen et al, 2020;Fu et al, 2020;Wu et al, 2015;Xu et al, 2008Xu et al, , 2014, and global stratosphere (Bian et al, 2020). In the boreal summer, convection is easy to be triggered, and clouds prevail over TP (Chen et al, 2019;Li et al, 2020;Li & Zhang, 2016;Liu et al, 2015;Wang et al, 2014;Yu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Fu et al (2020), the weather systems such as the shear line and low vortex, moisture as well as atmospheric stability especially before and after a precipitation should be focused in the future researches. Such the work could be seen from our current study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In order to explore the initialization and evolution mechanisms of local heavy snowfall over the Tibetan Plateau, a lot of research has been focused on water vapor and the thermodynamic and dynamic conditions (Zhang et al 2004;Dong et al 2018); cold and warm airflow convergence, low-level strong cyclonic vorticity, high-level divergence concurrent with low-level convergence, water vapor transportation and upward motion each play significant roles (Zou and Cao 1991;Shaman and Tziperman 2005;Dong et al 2018;Wang et al 2018). Additional to these atmospheric considerations, local topography strongly influences topographic snowfall (Zou and Cao 1991), and further study has been suggested on the energy and water vapor exchanges caused by complex terrain uplift (Fu et al 2020). These dynamic and thermodynamic factors need to be considered in concert to diagnose and analyze the evolution of heavy snowfall events; this understanding is foundational to the prediction and early warning of any local heavy snowfall event over the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the reanalysis data needs to be improved (Chen et al, 2015; You et al, 2015). More observations should be adopted to the models for more accurate simulations (Fu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%